Harnessing Knowledge-Based Concepts for Streamlined Mind Mapping in Academic Study - Weerasekara N.N; Senaweera T.I.S; Wijayasena W.D.N.D.T; Colambage K.G; Prasanna S. Haddela; Sathira Hettiarachchi (International Journal of Engineering and Management Research, 2023)
The main goal of this research project is to build and implement a knowledge-based system that will produce more accurate and significant mind maps from textual input. This study suggests the creation of a knowledge-based system devoted to mind map construction, as opposed to current text mining algorithms and machine learning techniques, which might not be able to properly capture the semantic subtleties of input material. The suggested system aims to reduce the constraints of conventional techniques by incorporating domain-specific information and rules into the analytical process. The accuracy and relevance of the produced mind maps are projected to improve with the addition of this knowledge. This project's main objective is to build a knowledge-based framework that overcomes the limitations of the existing text mining and machine learning approaches, resulting in more sophisticated and theoretically rich mind maps from textual data.